PEMBANGUNAN APLIKASI ANDROID PEMBELAJARAN REKA BENTUK GRAFIK DIGITAL - Hamzah, Norhasyimah; Zulkiflee, Siti Nadiah; Rubani, Siti Nur Kamariah; Ariffin, Arihasnida; Subramaniam, Tamil Selvan (Online Journal for TVET Practitioners, 2017)
Self-learning is one of the learning interests of students in the university. One of self-learning is through Mobile Learning (M-Learning). M-Learning is more of a self-directed learning tool using mobile devices such as mobile phones, personal assistants (PDAs), Palm Talk and others. The purpose of this study is to develop a Digital Graphic Design learning using android app and evaluate the functionality of the android graphic learning software application of Digital Graphics from aspects of information design, interface design and interaction design. ASSURE model is a guide in developing this android app where the ASSURE model has six components. This application was built using the Adobe Flash software, Adobe Photoshop and Camtasia Studio 8. Testing and evaluation was performed on three skilled experts in Digital Graphic Design and Creative Multimedia. In addition, thirty respondents from Faculty of Technical and Vocational Education, Universiti Tun Hussein Onn Malaysia (Creative Multimedia programed) students, the participated in the process of assessing customer satisfaction. In conclusion, this study can support students who want to learn independently through android applications.